Infusions of bicuculline to the ventral tegmental area attenuates sexual, exploratory, and anti-anxiety behavior of proestrous rats - Frye, Cheryl A. (2009)
Actions of 5α-pregnan-3α-ol-20-one (3α,5α-THP), in the midbrain ventral tegmental area (VTA) modulate sexual receptivity of female rats. Actions of 3α,5α-THP at GABAergic substrates in the VTA are known to modulate consummatory aspects of sexual behavior among rodents, such as lordosis. However, the extent to which GABA(A) receptors in the VTA are important for appetitive (exploratory, anti-anxiety, social) aspects of sexual-receptivity is not well-understood. Proestrous rats were bilaterally-infused with saline or bicuculline (100 ng), a GABA(A) receptor antagonist, to the VTA or missed-site control sites. Rats were assessed for exploratory/anti-anxiety (open field/elevated plus maze), social (social interaction), and sexual (paced-mating) behavior. Compared to saline or missed-site controls, intra-VTA bicuculline significantly reduced the number of central entries in an open field, time spent on the open arms of an elevated plus maze, frequency and intensity of lordosis, anti-aggression towards a male, pacing of sexual contacts, and 3α,5α-THP concentrations in midbrain and hippocampus. Bicuculline-infused rats also displayed less affiliation with a novel conspecific, fewer sexual solicitations, and had lower 3α,5α-THP concentrations in diencephalon and cortex, albeit these were not significant differences. Thus, actions at GABA(A) receptors in the midbrain VTA are essential for appetitive and consummatory aspects of sexual receptivity among rats.